Effectiveness of Nivolumab and Pembrolizumab as PD-1 Inhibitors in Unresectable or Metastatic Advanced Melanoma: A Systematic Review - Naomi Winny Tioline; Subagio Subagio; Wita Zahara (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Advanced melanoma is associated with poor prognosis because of limited effective treatment options, however, programmed cell death protein-1 inhibitors have transformed therapeutic strategies and significantly improved patient survival. Objective: This study aimed to evaluate the clinical effectiveness of nivolumab and pembrolizumab in patients with unresectable or metastatic advanced melanoma. Method: A systematic review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses 2020 guidelines using PubMed, ScienceDirect, and Wiley Online Library to identify studies published between 2020 and 2026. Clinical trials, randomized controlled trials, cohort studies, and single-arm studies reporting overall survival, progression-free survival, or objective response rate were included. Result and Discussion: wenty studies were included. PD-1 inhibitor monotherapy significantly improved overall survival versus ipilimumab (pembrolizumab: 32.7 vs. 15.9 months; nivolumab: 36.9 vs. 19.9 months). Nivolumab plus ipilimumab achieved overall survival exceeding 70 months with objective response rates up to 58%. Nivolumab combined with relatlimab improved progression-free survival (10.2 vs. 4.6 months) compared with monotherapy. Nivolumab also remained effective in brain metastases, though some combinations increased toxicity without added benefit. Conclusion: Nivolumab and pembrolizumab provide significant clinical benefits in unresectable or metastatic advanced melanoma by improving survival and treatment response